Pelayanan Diakonia Lintas Agama Berdasarkan Gagasan Karl Rahner Tentang Gereja Universal - Christoper, Ethan; Harisantoso, Imanuel Teguh (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2023)
One of the duties of the church is to carry out deaconess, which is to provide services to people experiencing distress. However, the church tends only to carry out internal deaconess to its members. In Indonesia, most churches have a pluralistic social environment with different religious communities. The research intends to examine the possibility of cross-religious deaconess based on Karl Rahner's idea of universal ecclesiology. The research method used is a literature study. The data was taken by tracing Rahner's central concept of universal ecclesiology, especially the anonymous Christian idea, on secondary sources. The research results show that interfaith deaconess is possible because it manifests the mysterious existence of God's work of salvation. Faith in God is not a metaphysical-abstract hope but accurate in historical experience. Deaconess across religions also illustrates the presence of the Triune God, who is always in His relationship with humans. The Triune God is not isolated but is present in the actions of the church's faith in society.